The Influence Mechanism of In Situ Stress State on the Stability of Deep-Buried-Curved Tunnel in Qinghai-Tibet Plateau and Its Adjacent Region - Huiqing Wang; Chengxuan Tan; Chengjun Feng; Peng Zhang; Bangshen Qi; Zhangliang Tan; Jing Meng; Weijun Guo (Shock and Vibration)
In China, rockburst disaster occurs mostly in construction of underground engineering in Qinghai-Tibet Plateau and its adjacent region. Previous research on deep-buried tunnels has indicated that tunnels stability is related to in situ stress state. To quantify these relationships, three-dimensional finite element modeling was done to analyze the influences that the angle φ between the maximum horizontal principal stress orientation and tunnel axis, and the lateral pressure coefficient KH, had on the tangential stress σθ in a deep-buried-curved tunnel. Based on the in situ stress condition in Qinghai-Tibet Plateau and its adjacent region, 50 different simulation conditions were used to analyze the relationship that φ and KH had on σθ for the rock mass surrounding the tunnel. With the simulation data produced, predictive equations were generated for σθ as a function of φ and KH using multivariate regression analysis. These equations help estimate σθ at various key positons along the tunnel boundary at Qinghai-Tibet plateau and its adjacent region. The equations were then proved by a set of typical tunnels to ensure validity. The results concluded that the change in φ has a significant impact on σθ, and thus, the stability of the tunnel, when 30° < φ < 60°, with the most obvious influence being when φ is about 45°. With the equations, the rockburst potential at a certain location within a curved tunnel can be quickly estimated by calculating φ and KH on σθ, without need of geo-stress background knowledge and heavy simulation, allowing for the practical value in engineering at design phase for the projects in Qinghai-Tibet Plateau and its adjacent region.